PW 2293 The development of a suitable portfolio of drowning reduction interventions for use by new and developing organisations in lmic's. (November 2018) - Williams, Darren; Power, John
Abstract : An estimated 3 60 000 people fatally drown each year worldwide. The causes are often connected to daily activities like washing, bathing, playing and collecting water – and over 90% of these deaths happen in low- and middle-income countries. The World Health Organisation (WHO) estimates that drowning rates in sub-Saharan Africa are 10 times higher than in the UK. Despite this, global drowning is essentially a 'silent epidemic', barely recognised on the global health or development agenda. These deaths are largely preventable. The challenge is that nearly all traditional lifesaving interventions have been designed specifically for established and well-resourced entities based in high income countries. Most of these interventions are nontransferable, as often there is a need for expensive equipment, well established infrastructure, meaning they will not be appropriate or sustainable. The aim of the presentation is to share the RNLI's experience in developing a portfolio of suitable lifesaving interventions, and to facilitate a discussion with attendees investigating ways to disseminate these interventions to those that need them. Since 2012 the RNLI has actively designed and delivered a number of lifesaving solutions for lower resource settings. Interventions include Lifeguarding, Maritime Search and Rescue, Aquatic Survival (learn to swim) and Flood Rescue. They have been developed in consultation and partnership with others to ensure they are suitable for the local operating context. Each intervention is a complete training package, which includes Train the Trainer and service implementation guidance, which are focused on new and developing organisations. Through the presentation the RNLI will have the opportunity to pitch the lifesaving interventions to an audience of subject matter experts and to gain valuable feedback to assist with the dissemination strategy of these interventions Attendees will have a better understanding of the interventions available to them to support their work (if required).